Composición de la flora en el CIEFOR " El Huayo" y varillal alto seco y su relación con la abundacia de especies de la familia Dendrobatidae (Anura: anfibia), Loreto - Perú - Cabudivo Escobar, Neil Anders (2022)
From January to september 2020 we are performed observations in the Forestry Research and Teaching Center (CIEFOR) “El Huayo” and the White sand forest in the National Reserve Allpahuayo Mishana (Perú) to know the composition of the flora and its relation with the abundance of species family Dendrobatidae, by direct observation. In the CIEFOR there are a richness of 118 species of plants with presence Aechmea moorei (Bromeliaceae) as epiphyte and VAS 121 species of plants with Aechmea nidularioides (Bromeliaceae) in the soil; in the CIEFOR and VAS was report 3 species of the family Dendrobatidae: Ranitomeya reticulata, Ranitomeya amazonica and Ameerega hahneli, where Ranitomeya reticulata report a density greater than the other species. We conclude that the flora CIEFOR and VAS they favor the survival and abundance of Ranitomeya reticulata, Ranitomeya amazonica and Ameerega hahneli.